Sources of School Income at The Jam'iyah Mahmudiyah Foundation - Nurika Khalila Daulay; Amiruddin Siahaan; Isra Adawiyah Siregar; Lia Ariska Ritonga; Maidiana Maidiana (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to determine the source of school income Jam'iyah Mahmudiyah Foundation. This research seeks to explain how the source of school income for the Jam'iyah Mahmudiyah Foundation is. The method used in this research is qualitative. Data collection techniques using observation techniques, interviews, and documentation study techniques to obtain valid data about the source of school income. This research was conducted at MTs Jam'iyah Mahmudiyah which is located on Jl. Sheikh M. Yusuf, Tanjung Pura District. The results of the study indicate that the sources of school income at the Jam'iyah Mahmudiyah Foundation are divided into three, namely school income from the government, school income from students' parents, and income from independent school businesses obtained from several activities such as the management of the school canteen so that the sales or rental income where the sale will be collected so that it becomes a source of income. Then the management of school cooperatives and the rental of school-owned buildings and facilities which of course can become income for the foundation itself.